EVALUASI TARIF DAN MUTU PELAYANAN ANGKUTAN ANTAR PROVINSI (Studi Kasus: Angkutan Minibus Jurusan Puruk Cahu – Banjarmasin) - Maretina Eka Sinta (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
Central Kalimantan Province especially Murung Raya is an area with abundant natural resources, require transportation facilities and infrastructure, especially more emphasized in the field of land transportation. In this case, it is necessary to evaluate the tariff and quality of transportation service between provinces to know the conformity of current tariff and the quality of transportation service. Data collection was conducted through surveys and interviews conducted in Puruk Cahu. The purpose of this research is to know the amount of Vehicle Operation Cost of public transportation from Puruk Cahu to Banjarmasin so that the amount of passenger tariff that match with Vehicle Operating Cost is incurred and also know the quality of service from transportation service provider side. Based on the result of Vehicle Operation Cost Analysis (VOC) of Puruk Cahu Public Transportation to Banjarmasin, the basic cost per day is Rp 991.384.08, -/ transportation/ day, the basic rate every person is Rp 165,230.68, - / person / trip , the basic tariff of public transport is Rp 181,753.75, - / person / trip, so with the applicable tariff of Rp 250,000 / person providing a reasonable income for the transportation service provider and for the passengers is reasonable. Keywords : Vehicle Operational Cost (VOC), evaluation, tariff